State of precision medicine for heart failure with preserved ejection fraction in a new therapeutic age - Roy Rasalam; Andrew Sindone; Gary Deed; Ralph G. Audehm; John J. Atherton (ESC Heart Failure)
Abstract Heart failure with preserved ejection fraction (HFpEF) is defined by heart failure (HF) with a left ventricular ejection fraction (LVEF) of at least 50%. HFpEF has a complex and heterogeneous pathophysiology with multiple co‐morbidities contributing to its presentation. Establishing the diagnosis of HFpEF can be challenging. Two algorithms, the ‘Heavy, 2 or more Hypertensive drugs, atrial Fibrillation, Pulmonary hypertension, Elderly age >60, elevated Filling pressures’ (H2FPEF) and the ‘Heart Failure Association Pre‐test assessment, Echocardiography and natriuretic peptide, Functional testing, Final aetiology’ (HFA‐PEFF), can help to determine the likelihood of HFpEF in individuals with symptoms of HF. Phenotype clusters defined largely by the total number and types of co‐morbidities may delineate groups of patients with HFpEF with different management needs. It is important to recognize alternative diagnoses or HFpEF mimics such as infiltrative cardiomyopathies, coronary artery disease, lung disease, anxiety, depression, anaemia, severe obesity, and physical deconditioning, among others. Treatment with sodium‐glucose co‐transporter 2 inhibitors (dapagliflozin and empagliflozin) is recommended for all patients with HFpEF unless contraindicated. Future research should consider alternative approaches to guide the initial diagnosis and treatment of HFpEF, including phenotype clustering models and artificial intelligence, and consider whether LVEF is the most useful distinguishing feature for categorizing HF. Ongoing clinical trials are evaluating novel pharmacological and device‐based approaches to address the pathophysiological consequences of HFpEF.